(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
The article analyzes the operation of the distillation column plates used in the chemical and oil refining industries and suggests the use of plates with a new design. According to the experimental results, the hydraulic resistance of the plates of the new design is smaller than the hydraulic resistance of the traditional plates.